2016
DOI: 10.1002/2015jd024334
|View full text |Cite
|
Sign up to set email alerts
|

Using in situ airborne measurements to evaluate three cloud phase products derived from CALIPSO

Abstract: We compare the cloud detection and cloud phase determination of three independent climatologies based on Cloud-Aerosol Lidar and Infrared Pathfinder Satellite Observation (CALIPSO) to airborne in situ measurements. Our analysis of the cloud detection shows that the differences between the satellite and in situ measurements mainly arise from three factors. First, averaging CALIPSO Level l data along track before cloud detection increases the estimate of high-and low-level cloud fractions. Second, the vertical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
78
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(85 citation statements)
references
References 83 publications
(125 reference statements)
7
78
0
Order By: Relevance
“…Second, polar cloud phase is not well known, and the processes underlying phase transitions in current and warming climate are hard to observe and predict from first principles. Thus, CALIPSO cloud phase observations are especially important in polar regions [30] and have been vetted against in situ airborne measurements [31]. Third, polar hydrometeors cover surfaces with highly variable albedos and albedos that are changing in a warming world (e.g., as a consequence of sea ice loss).…”
Section: Observational Advances For Arctic Clouds Over the Last Decadementioning
confidence: 99%
“…Second, polar cloud phase is not well known, and the processes underlying phase transitions in current and warming climate are hard to observe and predict from first principles. Thus, CALIPSO cloud phase observations are especially important in polar regions [30] and have been vetted against in situ airborne measurements [31]. Third, polar hydrometeors cover surfaces with highly variable albedos and albedos that are changing in a warming world (e.g., as a consequence of sea ice loss).…”
Section: Observational Advances For Arctic Clouds Over the Last Decadementioning
confidence: 99%
“…Cesana and Chepfer (2013) indicated that these "undefined" samples account for about 10.3 % of cloudy pixels in 15 months of global statistics. In addition, because lidar cannot penetrate optically thick clouds (optical depth > 3, such as the supercooled liquid layer in the polar region) to detect ice crystals (Zhang et al, 2010), the CALIPSO-GOCCP cloud phase products possibly lead to a slight underestimation of ice clouds at the lowest levels at Arctic (Cesana et al, 2016).…”
Section: Cloud Phase Productmentioning
confidence: 99%
“…Choi et al (2010) has pointed out that this definition may lead to some overestimation of SCFs without considering horizontally oriented ice particles, which account for about 10 % of the uncertainty in their study. However, the impact of the oriented ice crystals on the determination of cloud phase is negligible after tilting the CALIOP to 3 • off-nadir (November 2007) Cesana et al, 2016).…”
Section: Cloud Phase Productmentioning
confidence: 99%
“…The high confidence criteria imposed to the CALIOP cloud phase (see below) shall, however, constrain the selected cloud and cloud profiles to high confidence liquid and high confidence ice clouds. Nevertheless, especially at high latitudes, an uncertainty remains due to the difficult cloud phase determination (Cesana et al, 2016).…”
Section: Vertical Cloud-aerosol Structures From Caliopmentioning
confidence: 99%